Analisis tanggung jawab Operator tour dalam menjalankan paket wisata petualangan dilihat dari aspek-aspek hukum di Indonesia - Padriadi Wiharjokusumo (Akademi Pariwisata Darma Agung, 2018)
Tourists are the consumers of the services of Tour and Travel company. With its position as a consumer, where the position between tourists and the Tour and Travel company is opposite. Tourists need to have legal protection that can provide a sense of security in the use of services provided by the Tour and Travel company. which in this case acts as a producer. It does not have to be denied, however, that the number of tourists who use the services of Tour and travel company are often neglected their rights. Whereas it is very clear that the right of tourists is regulated in Article 20 of Law Number 10 of 2009 on Tourism.